Isolation and identification of regulatory T cells in peripheral blood of rhesus monkeys - Zhang, S.; Jin, X.; Cheng, H.; He, S.; Chen, Younan; Long, D.; Shan, J.; Zeng, L.; Wang, C.; Cheng, J.; Lu, Y. (2012)
Objective: To establish a method to isolate the CD4+CD25+ regulatory T cells (Tregs) and to identify the purity and function of these cells. Methods: The peripheral blood (8 mL) were collected from the great saphenous vein of 10 rhesus monkeys (4 females and 6 males, aged 4-5 years, and weighing 5-8 kg). The mononuclear cells were isolated with density gradient centrifugation. CD4+ T cells were separated by the Magnetic cell sorting (MACS) negative selection and MACS positive selection. The cell yield rate, the cell viability, and the cell purity were compared between MACS negative selection and MACS positive selection. In CD4+ MACS negative selection, the anti-biotin MicroBeads and biotin-antibody cocktai in CD4+CD25+ Tregs isolation kit non-human primate were used, and in MACS positive selection, the anti-APC MicroBeads in CD4+CD25+ Tregs isolation kit non-human primate and CD4-APC were used. The CD4+ T cells separated by positive selection were selected to obtain CD4+CD25 Tregs with CD25 MicroBeads. The purity, activity, the FoxP3 level, and the suppressive function to concanavalin A (ConA) activated autologous CD4+CD24 effective T cells (Teffs) of CD4+CD25+ Tregs were detected by flow cytometry.Results: After CD4+ T cells were separated by MACS negative selection and MACS positive selection, the cell viabilities were all up to 95%, showing no significant difference (P > 0.05). The cell yield rate and purity of CD4+ T cells by positive selection were significantly higher than those of CD4+ T cells by negative selection (P < 0.05). CD4+CD25+ Tregs can be successfully isolated by MACS double positive selection. The classifying purity was 76.2% +/- 8.6%; the cell activity was 93.3% +/- 4.7%; and the level of FoxP3 was 74.2% +/- 6.9%. The CD4+CD25+ Tregs had suppressive effect on ConA activated autologous CD4+CD25 Teffs. Conclusion: MACS double positive selection can be used to isolate high-purity CD4+CD25+ Tregs from the peripheral blood of rhesus monkeys and the process does not influence the activity of CD4+CD25+ Tregs.